British mapping of Africa: publishing histories of imperial cartography, c. 1880 – c. 1915 - Prior, Amy Dawn (The University of Edinburgh, 2013)
This thesis investigates how the mapping of Africa by British institutions between c.1880 and c.1915 was more complex and variable than is traditionally recognised. The study takes three ‘cuts’ into this topic, presented as journal papers, which examine: the Bartholomew map-publishing firm, the cartographic coverage of the Second Boer War, and the maps associated with Sir Harry H. Johnston. Each case-study focuses on what was produced – both quantitative output and the content of representations – and why. Informed by theories from the history of cartography, book history and the history of science, particular attention is paid to the concerns and processes embodied in the maps and map-making that are irreducible to simply ‘imperial’ discourse; these variously include editorial processes and questions of authorship, concerns for credibility and intended audiences, and the circulation and ‘life-cycles’ of maps. These findings are also explored in relation to the institutional geography of cartography in Britain: the studies illustrate the institutional contingency of such factors and how this gave rise to highly variable representations of Africa. These three empirical papers represent the first sustained studies of each of the topics. By connecting their findings, the thesis also offers broader reconceptualisations of the British mapping of Africa between c.1880 and c.1915: with respect to cartographic representations, maps as objects, and the institutions producing them. Maps did not simply reflect ‘imperial’ discourse; they were highly variable manifestations of multifaceted and institutionally contingent factors and were mobile and mutable objects that were re-used and re-produced in different ways across different settings. Mapmaking institutions were discrete but interconnected sites that not only produced different representations, but played different roles in the mapping of Africa. By illuminating the institutional provenance, ‘life-cycles’ and content of the maps studied, this thesis extends current knowledge of British mapping of Africa during the late nineteenth and early twentieth centuries and raises questions for further research incorporating its lessons, sources and theories.
Keywords: map history; history of the book; Second Boer War; Johnston, Harry Hamilton, 1858-1927; Bartholomew (Firm)